The Influence of Money Politics on Voter Behavior During Regional Head Elections (Pilkada) in South Sulawesi Province - Anugrah, Mutmainnah Gaffar (Moccasin Journal De Public Perspective, 2025)
Money politics, the practice of distributing material incentives to sway voter decisions, has long been a challenge in Indonesian elections. This study examines the influence of money politics on voter behavior during the regional head elections in South Sulawesi. Using a mixed-methods approach, the study combines quantitative surveys and qualitative interviews to assess the prevalence of money politics and its impact on voting choices. The findings reveal that 61.1% of respondents were exposed to financial inducements, and lower-income voters were particularly susceptible to material rewards. The study also highlights the socio-cultural reinforcement of money politics, with local leaders playing a key role in distributing incentives and social norms of reciprocity shaping voter behavior. Despite these challenges, some voters demonstrated ethical awareness, suggesting that voter education could play a role in mitigating the impact of money politics. The study contributes to the broader literature on clientelism, emphasizing the need for both legal reforms and socio-economic changes to address the root causes of money politics. Future research could investigate the effectiveness of voter education programs and explore broader reforms to enhance electoral integrity.